Genome-wide identification of aquaporin encoding genes in Brassica oleracea and their phylogenetic sequence comparison to Brassica crops and Arabidopsis - Diehn, Till A.; Pommerrenig, Benjamin; Bernhardt, Nadine; Hartmann, Anja; Bienert, Gerd P. (Frontiers in Plant Science, 2015)
Aquaporins (AQPs) are essential channel proteins that regulate plant water homeostasis and the uptake and distribution of uncharged solutes such as metalloids, urea, ammonia and carbon dioxide. Despite their importance as crop plants, little is known about AQP gene and protein function in cabbage (Brassica oleracea) and other Brassica species. The recent releases of the genome sequences of B. oleracea and B. rapa allow comparative genomic studies in these species to investigate the evolution and features of Brassica genes and proteins. In this study, we identified all AQP genes in B. oleracea by a genome-wide survey. In total, 67 genes of four plant AQP subfamilies were identified. Their full-length gene sequences and locations on chromosomes and scaffolds were manually curated. The identification of six additional full-length AQP sequences in the B. rapa genome added to the recently published AQP protein family of this species. A phylogenetic analysis of AQPs of A. thaliana, B. oleracea, B. rapa allowed us to follow AQP evolution in closely related species and to systematically classify and (re-) name these isoforms. Thirty-three groups of AQP-orthologous genes were identified between B. oleracea and Arabidopsis and their expression was analyzed in different organs. The two selectivity filters, gene structure and coding sequences were highly conserved within each AQP subfamily while sequence variations in some introns and untranslated regions were frequent. These data suggest a similar substrate selectivity and function of Brassica AQPs compared to Arabidopsis orthologs. The comparative analyses of all AQP subfamilies in three Brassicaceae species give initial insights into AQP evolution in these taxa. Based on the genome-wide AQP identification in B. oleracea and the sequence analysis and reprocessing of Brassica AQP information, our dataset provides a sequence resource for further investigations of the physiological and molecular functions of Brassica crop AQPs.